Role of trees in climate change and their authentication through scanning electron microscopy - Arshad, S. (2019)
Climate change is the most realistic theory of this era. Sudden and drastic changes are happening on the earth and the survival of mankind is becoming questionable in the future. The plants play the key role in controlling the climate change. The study emphasizes on role of trees in the cop up or damaging the climate of this earth, whether they are medicinal trees or economically important trees. Due to the overgrazing and intense deforestation the climate is being affected hazardously. The global warming phenomenon is occurring due to the less availability of trees and more carbon dioxide in the atmosphere. In total 20 plants were collected from across the Pakistan on the basis of their abundance and their key roles. Out of which seeds of eight plants were scanned through scanning electron microscope for correct authentication and importance of these medicinally important trees in mitigating the climate change. Research Highlights: The role of forest sector in the climate's change mitigation. Medicinally and economically important tree species across Pakistan. By using SEM, Ultra seed sculpturing features as an authentication tool. To formulate some policies to stop or control deforestation. Â© 2018 Wiley Periodicals, Inc.